2022
DOI: 10.7235/hort.20220058
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Amount of Nitrogen Fertilizer for Shading Cultivation of Tea Tree Seedlings

Doobo Shim,
Seung Ho Jeon

Abstract: Nitrogen fertilizers are essential for productivity and quality improvement of all crops. However, excessive nitrogen can cause physiological disturbances. Therefore, depending upon the type of crop and cultivation method, controlling the amount of fertilizer is important. Typically, the proper amount of nitrogen fertilizer is determined by the organic matter content of the soil in which the plants (tea plants in our case) are grown. However, there is no difference in the amount of fertilizer applied during sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Chlorophyll fluorescence analysis is one of the methods to identify plant stress levels and the inactivity of the reaction center of photosystem II (PSII), which can be done in the non-destructive investigation (Lechaudel et al, 2010;Shim and Jeon, 2022). Chlorophyll fluorescence analysis that had been applied in various studies in the past had its usefulness proved by being used in assessing the photosynthetic efficiency and stress of plants through various fluorescence parameters such as F v /F m , Φ Do , ABS/RC, DI o /RC, and PI ABS (An et al, 2022;Choi et al, 2022;Kwon et al, 2021;Oh and Lee, 2022;Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll fluorescence analysis is one of the methods to identify plant stress levels and the inactivity of the reaction center of photosystem II (PSII), which can be done in the non-destructive investigation (Lechaudel et al, 2010;Shim and Jeon, 2022). Chlorophyll fluorescence analysis that had been applied in various studies in the past had its usefulness proved by being used in assessing the photosynthetic efficiency and stress of plants through various fluorescence parameters such as F v /F m , Φ Do , ABS/RC, DI o /RC, and PI ABS (An et al, 2022;Choi et al, 2022;Kwon et al, 2021;Oh and Lee, 2022;Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies were conducted on the growth of succulent plants according to shading levels (Lee et al, 2021b;2022c;Nam et al, 2022), the effect of shading treatment on the growth of ornamental flower crops (Jang et al, 2022;Kwon et al, 2020;Park and Kim, 2021), and adequate shading levels for vegetables and tea tree (Cao et al, 2022;Shim and Jeon, 2022;Sim et al, 2021). As such, studies reported different results for various plant species, and it is also necessary to investigate the most suitable shading level for the cultivation of M. cordifolium f.…”
Section: Introductionmentioning
confidence: 99%